Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1093/pcp/pcs080
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of Leaf Morphology by MicroRNA394 and its Target LEAF CURLING RESPONSIVENESS

Abstract: The present study identified Arabidopsis miR394 and its target, an F-box (SKP1-Cullin/CDC53-F-box) gene At1g27340 (here referred to as LEAF CURLING RESPONSIVENESS, LCR), for regulation of leaf curling-related morphology. The loss-of-function lcr mutants exhibit pleiotropic defects with semi-dwarfism, altered leaf shape and a shorter stem. Overexpression of an miR394-resistant version of LCR under the 35S promoter (35S:m5LCR) and target mimicry MIM394 resulted in a curled-down leaf defect. Conversely, transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
81
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 56 publications
3
81
0
1
Order By: Relevance
“…by targeting LEAF CURLING RESPONSIVENESS {LCR} gene). It is known to be drought responsive in Arabidopsis and other species (Song et al 2012;Liu et al 2008;Kantar et al 2011;Shuai et al 2013). Upregulation of miR394 in J. pentantha is comparable to those reported in cotton (0.87 fold increase) exposed to drought stress (Xie et al 2014).…”
Section: Resultssupporting
confidence: 64%
“…by targeting LEAF CURLING RESPONSIVENESS {LCR} gene). It is known to be drought responsive in Arabidopsis and other species (Song et al 2012;Liu et al 2008;Kantar et al 2011;Shuai et al 2013). Upregulation of miR394 in J. pentantha is comparable to those reported in cotton (0.87 fold increase) exposed to drought stress (Xie et al 2014).…”
Section: Resultssupporting
confidence: 64%
“…By contrast, miR172, miR396, miR5020, miR5629, miR5645, and miR5648 showed significant down-regulation in the 35S::SAP11 AYWB transgenic plants. Among them, miR2111, miR399, and miR827 have been shown to be up-regulated by Pi starvation (Hsieh et al, 2009;Pant et al, 2009), and miR399 and miR827 play important roles in regulating Pi homeostasis (Liu et al, 2012;Huang et al, 2013;Lin et al, 2013); miR160 and miR396 are required for regulating the auxin signaling response and cell proliferation during leaf and root development (Gutierrez et al, 2009;Pulido and Laufs, 2010;Debernardi et al, 2012;Bazin et al, 2013); miR172 has been shown to regulate the transition from the vegetative to reproductive phases (Aukerman and Sakai, 2003;Wu et al, 2009); and miR394 is required for the regulation of leaf morphology and shoot meristem stem-cell maintenance (Song et al, 2012;Knauer et al, 2013). However, miR5020b, miR5629, miR5639, miR5645d, miR5648, miR5655, and miR850 are newly identified miRNAs with unknown functions.…”
Section: Genome-wide Identification Of Differentially Expressed Mirnamentioning
confidence: 99%
“…In Arabidopsis, miR394 targets the F-box gene LEAF CURLING RESPONSIVENESS and functions as a mobile signal to establish stem cell niche organization (Song et al, 2012;Knauer et al, 2013). In maize, miR394 is predicted to target the F-box genes GRMZM2G119650 and GRMZM2G064954, both of which are broadly expressed during maize development, including in inflorescences (Sekhon et al, 2011).…”
Section: Mirnas Are Required Broadly During Inflorescence and Vegetatmentioning
confidence: 99%